STUDY OF UTILIZATION OF FISH LANDING FACILITIES KARYA BARU AND ROBIN IN CONCONG LUAR SUB-DISTRICT, CONCONG DISTRICT, INDRAGIRI HILIR REGENCY, RIAU PROVINCE - Chintami Puspita Adi; Alit Hindri Yani; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe study was conducted in February and June 2019 at the Fish Landing Places in Concong Luar Sub-District by using survey method. The survey was conducted at 2 sample Fish Landing Places units which categorized as large. The aims of this study to determine the facilities and activities as well as the level of utilization of facilities. The results showed that the facilities available at the Karya Baru Fish Landing Places such as dock, cold storage, fuel stations, clean water tanks, production shelter rooms, electricity networks, net storage, MCK, guard posts, multipurpose rooms and parking lots. While at the Robin Fish Landing Places such as dock, ice factories, fuel stations, clean water tanks, ice storage, electricity networks and ice crusher machines. The utilization rate for each facilities between 15,93% to 150,29%. The Fish Landing Places activities are landing fish, catch handling, anchor mooring, fish marketing, repair and maintenance of ships and fishing gear and supplies replenishment at sea.Keywords:Fish Landing Places, Facilities and Activities, Utilization Rate of Facilities.